Motor variability in sports: A non-linear analysis of race walking - Preatoni, E.; Ferrario, M.; Dona, G.; Hamill, J.; Rodano, R. (Journal of Sports Sciences, 2010)
This aim of this study was to analyse the nature of movement variability and to assess whether entropy measures may represent a valuable synthetic index of neuromuscular organization. The regularity of kinematic/kinetic time series during race walking, the changes in the structure of intra-individual variability over the test session, and the influence of athletic skill in (inter)national rank athletes were investigated. Motion analysis techniques were used. Sample entropy (SampEn) was adopted to examine fluctuations in lower limb angles and ground reaction forces. The regularity of both original and surrogate time series was assessed and compared, by estimating SampEn, to verify the presence of non-linear features in movement variability. SampEn was statistically lower in the original data than in surrogates. In contrast, the regularity of time series did not change significantly throughout the subsequent intra-individual repetitions. Hip and ankle joint angles and vertical ground reaction force manifested increased entropy for skilled athletes. Results suggest that race walking variability was not only the product of random noise but also contained information about the inherent propriety of the neuro-musculo-skeletal system. Furthermore, they provide some indications about neuromuscular control of the lower limb joints during race walking gait, and about the differences between more and less skilled individuals.